2013
DOI: 10.1038/ejhg.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Cellular imaging demonstrates genetic mosaicism in heterozygous carriers of an X-linked ciliopathy gene

Abstract: X-linked retinitis pigmentosa (XLRP) is the least common genetic type of retinitis pigmentosa; however, it has extremely devastating consequences to patients' activities of daily living. RPGR and RP2 genes expressed in the photoreceptor sensory cilia are predominantly implicated in XLRP; however, the interpretation of genetic mutations and their correlation with clinical phenotypes remain unknown, and the role of these genes in photoreceptor cilia function is not completely elucidated. Therefore, we evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…; Zheng et al. ; Pyo Park et al ). Precision medicine requires highly accurate phenotype–genotype correlations that could be enhanced with new imaging and DNA sequencing modalities.…”
Section: Introductionmentioning
confidence: 99%
“…; Zheng et al. ; Pyo Park et al ). Precision medicine requires highly accurate phenotype–genotype correlations that could be enhanced with new imaging and DNA sequencing modalities.…”
Section: Introductionmentioning
confidence: 99%
“…8-10,14 Presumably none of the cones in either the hyperreflective lesions or the dark areas were detected. Unfortunately, neither manual nor automatic calculation methods for cone density have been developed for our second prototype of AO-SLO.…”
Section: Discussionmentioning
confidence: 98%
“…As the normal appearance of cone cells external to the dark lesions, these lesions may not alter overall visual acuity, which is a function of the entire retina. 14 Also, the dark lesions were too small to be detected by microperimetry. Nonetheless, the decreased autofluorescence on FAF images likely represented a mild reduction in sensitivity attributable to RPE dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, AOSLO provided rare insight into the cellular organization of retinas in patients with chloroquine retinopathy, acute posterior multifocal placoid pigment epitheliopathy (APMPPE), enhanced S-cone syndrome, and X-linked retinitis pigmentosa (XLRP) [1821]. Using AOSLO, Duncan et al reported increased cone spacing and abnormal packing in the macula of XLRS patients [22].…”
Section: Discussionmentioning
confidence: 99%